Peningkatan Mutu Proses Perguruan Tinggi Melalui Sistem Mutu Iso 9000 - Th. Widia Soerjaningsih (Bina Nusantara University, 2004)
Article was made to answer these several questions; what is acreditation and the application in the college; what is ISO 9000 quality system; why is ISO 9000 needed by the college; how ISO 9000 can support the achievement of the defined quality level; how ISO 9000 guarantee the achievement of BAN target including quality, efficiency, and relevance; what is the difference between BAN Acreditation and ISO 9000 Certification; ISO 9000 Consultant: why it is necessary, how to choose it, the line of the contract; ISO 9000 Assessor and the achieve certification: SGS and etc.; and ISO 9000 Certification Proccess Cost Aspect.